DOES PRESTERILIZATION HAS ANY INFLUENCE ON CONSERVATIVE AND ENDODONTIC MATERIAL STERILITY, IMMEDIATELY AFTER UNPACKING AND POST EXPOSURE TO CLINICAL ENVIRONMENT FOR 15 DAYS - AN EX VIVO STUDY. - S. Anitha Rao,; Deepthi Angalakuditi,; Sunehra Sanam,; K Santhosh Reddy,; Sabavat Sangeetha, (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Instruments used in the operative area are colonised by various microbial organisms during usage. Sterilization is an important prerequisite to avoid cross contamination.Purpose of the study: The purpose of this study was to evaluate whether presterilization has any influence on conservative and endodontic material sterility, immediately after unpacking and post exposure to clinical environment for 15 days.Methods: Gutta percha cones, Rubber dam clamps, Impression trays, Dental burs (#245 bur, Access opening bur) were tested.Materials were randomly sampled at 2 time points (t0, at package opening; t1, at 15days) during their clinical usage. Vortexing, centrifuging, streak and inoculation was done. Colony formation under aerobic conditions was observed on media before and after presterilization.Statistical analysis: Wilcoxon matched pairs test was done for comparison of data before and after pre sterilization with status of aerobic organisms at to (immediately after opening) and t1 (during clinical usage).Conclusion: Presterilization effectively eliminates cross contamination of various aerobic microorganisms in conservative and endodontic material immediately unpacked and post exposure to clinical environment for 15 days.